2004
DOI: 10.1074/jbc.m410073200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Kelch Domain of Human Keap1

Abstract: Keap1 is a substrate adaptor protein for an ubiquitin ligase complex that targets the Nrf2 transcription factor for degradation. Keap1 binds Nrf2 through its C-terminal Kelch domain, which contains six copies of the evolutionarily conserved kelch repeat sequence motif. The structure of the Kelch domain from human Keap1 has been determined by x-ray crystallography to a resolution of 1.85 Å. The Kelch domain forms a 6-bladed ␤-propeller structure, with residues at the C terminus forming the first strand in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
181
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(191 citation statements)
references
References 54 publications
8
181
0
Order By: Relevance
“…These results suggest that the inhibitory regulation effect of OsPPKL1 results from its Kelch domains. The Kelch domain has been reported to represent one β-sheet blade, and several repeats are able to interact to form a β-propeller (17). In rice, LARGER PANICLE (LP) encoding a Kelch repeat-containing F-box protein was reported to play a negative role in regulating plant architecture, particularly panicle architecture (18).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that the inhibitory regulation effect of OsPPKL1 results from its Kelch domains. The Kelch domain has been reported to represent one β-sheet blade, and several repeats are able to interact to form a β-propeller (17). In rice, LARGER PANICLE (LP) encoding a Kelch repeat-containing F-box protein was reported to play a negative role in regulating plant architecture, particularly panicle architecture (18).…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports by several groups have demonstrated that Keap1 functions as a substrate adaptor protein for a Cul3-Rbx1 E3 1 ubiquitin ligase complex (19 -22). The N-terminal BTB domain and central linker region of Keap1 bind Cul3, whereas the C-terminal Kelch domain of Keap1 binds Nrf2 via residues located within loops that extend out from the bottom of the Kelch domain (20,21,23). Under conditions of homeostatic cell growth, Keap1 brings Nrf2 into the Cul3-Rbx1 complex and enables ubiquitin conjugation onto specific lysine residues located within the N-terminal Neh2 domain of Nrf2 (21).…”
mentioning
confidence: 99%
“…Human Keap1 is a 70-kDa cysteine-rich protein (624 amino acids and 27 cysteines), comprising five domains: (i) N-terminal region (NTR), (ii) BTB (broad complex, tramtrack, or bric-a-brac), an evolutionarily conserved protein-protein interaction motif that often dimerizes with other BTB domains (20), (iii) intervening region (IVR), a cysteine-rich region, (iv) double glycine region (DGR), a domain that comprises six Kelch motifs and binds to the Neh2 domain of Nrf2 (21), and (v) C-terminal region (CTR). It is difficult to express soluble Keap1, which is highly prone to oxidation and oligomerizes easily.…”
mentioning
confidence: 99%